Endoscopic Knot‐Tying of the Nasal Cavity and Skull Base Without Special Instruments - Tomotaka Hemmi; Kazuhiro Omura; Kazuhiro Nomura; Teppei Takeda; Satoshi Aoki; Teru Ebihara (OTO Open)
Abstract This report introduces an endoscopic knot‐tying technique for a wide range of procedures, such as nasal mucosa suturing and dura mater reconstruction, without the need for specialized instruments. The technique utilizes basic tools like a needle holder, sutures, and bayonet‐shaped nasal forceps. The surgeon ties a surgeon's knot, guided by an endoscope, and pulls the suture with forceps to ensure proper tension. The method is effective in various surgeries, from septoplasty to skull base procedures, and has shown no adverse events in 137 patients. Its advantages include simplicity, no need for specialized tools, and ease of use in different facilities. The technique has the potential to advance endoscopic surgery, providing an efficient solution for diverse surgical applications.